Investigating Cognitive Levels on Reading Comprehension Questions in EFL Textbook for Merdeka Curriculum - Atina Firdausa Qisthi; Djatmika; Ngadiso (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research aims to examine the cognitive levels present in “Bahasa Inggris Work in Progress Buku Siswa Untuk SMA/SMK/MA Kelas 10.” It evaluates how they might influence the development of students' thinking skills. The study employed qualitative content analysis, using an analytical framework adapted from the revised Bloom’s Taxonomy to analyze 35 WH-questions from six selected chapters. This research primarily employed WH-questions as the primary data source, as they are highly valuable for promoting students' literal comprehension skills, rearranging text information, and developing evaluations, personal responses, and predictions. This research found that higher-order thinking skills (HOTS) were more dominant than lower-order thinking skills (LOTS) in the WH-questions. Furthermore, not all six levels of Bloom’s Taxonomy were represented. The cognitive level “Understand” becomes the most dominant in the textbook, followed by “Evaluate,” “Analyze,” and “Remember,” which are the least dominant cognitive levels found in the data. Conversely, the cognitive levels “Apply” and “Create” were not found in the examined data. These results suggest that while the textbook effectively promotes certain aspects of higher-order thinking, it lacks diversity in cognitive challenges. Therefore, teachers are encouraged to supplement the textbook with additional tasks that foster real-world application and creativity. Textbook designers should also integrate a broader range of cognitive levels to provide more comprehensive and balanced learning experiences aligned with the goals of the Merdeka Curriculum.